2022
DOI: 10.1002/hep.32277
|View full text |Cite
|
Sign up to set email alerts
|

Fat‐associated lymphoid clusters as expandable niches for ectopic liver development

Abstract: Background and Aims Hepatocyte transplantation holds great promise as an alternative approach to whole‐organ transplantation. Intraportal and intrasplenic cell infusions are primary hepatocyte transplantation delivery routes for this procedure. However, patients with severe liver diseases often have disrupted liver and spleen architectures, which introduce risks in the engraftment process. We previously demonstrated i.p. injection of hepatocytes as an alternative route of delivery that could benefit this subpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Fat-associated lymphoid clusters (FALCs) are a unique anatomical structure of the peritoneum, specifically localized in the omentum. FALCs are identified leukocyte aggregates, mainly composed of B and T lymphocytes and stromal cells, designed to maintain peritoneal homeostasis and mitigate local inflammation ( Han et al, 2022 ). These clusters of leukocytes possess the unique capacity to collect fluids, particles, and cells from the peritoneal cavity ( Buscher et al, 2016 ; Cruz-Migoni and Caamano, 2016 ; Liu M. et al, 2021 ; Terri et al, 2021 ).…”
Section: Intercellular Communicationmentioning
confidence: 99%
“…Fat-associated lymphoid clusters (FALCs) are a unique anatomical structure of the peritoneum, specifically localized in the omentum. FALCs are identified leukocyte aggregates, mainly composed of B and T lymphocytes and stromal cells, designed to maintain peritoneal homeostasis and mitigate local inflammation ( Han et al, 2022 ). These clusters of leukocytes possess the unique capacity to collect fluids, particles, and cells from the peritoneal cavity ( Buscher et al, 2016 ; Cruz-Migoni and Caamano, 2016 ; Liu M. et al, 2021 ; Terri et al, 2021 ).…”
Section: Intercellular Communicationmentioning
confidence: 99%
“…Due to the low cell survival in the harsh local microenvironment, we and others have previously shown that ectopically implanted liver mimics could increase the survival ratio of ALF-challenged animal models, ameliorate oxidative stress and inflammation, and herein advance liver regeneration. [10,12] Therefore, in this study we first subcutaneously implanted the biomimetic hepatic analogs near the inguinal fat pads with rich blood vessels to study their therapeutic efficacy in the treatment of CCl 4 -induced ALF (Figure 8a).…”
Section: Ectopic Implantation Of Vascularized Mini-livers For Rescue ...mentioning
confidence: 99%
“…Expansion of the number and size of FALCs could offer important therapeutic oportunities in the field of hepatocyte or islet transplantation into the omentum. [70][71][72] Hepatocyte engraftment in the omentum can be increased by inducing peritoneal inflammation to expand available FALCs for ectopic liver regeneration, 70…”
Section: Inflammation Driven Neoformation Of Falcsmentioning
confidence: 99%
“…How cross talk between inflammatory signals and stromal cells fine‐tune the number and function of FALCs is probably context dependent and remains to be elucidated. Expansion of the number and size of FALCs could offer important therapeutic oportunities in the field of hepatocyte or islet transplantation into the omentum 70–72 . Hepatocyte engraftment in the omentum can be increased by inducing peritoneal inflammation to expand available FALCs for ectopic liver regeneration, 70 demonstrating the relevance of the approach but highlighting the need to identify factors promoting FALC niche expansion without inducing acute inflammation.…”
Section: Mechanisms Regulating Falc Formationmentioning
confidence: 99%